A co-extruded foam board and preparation method thereof
Through the preparation method of co-extruded foaming plate, a multi-stage crosslinking network is formed using materials such as polyurethane masterbatch, flame retardant crosslinking agent and modified magnetic bamboo charcoal powder, which solves the problems of flammability and electromagnetic pollution of existing polyurethane foam materials, and achieves high-performance flame retardant, heat insulation, sound insulation and electromagnetic protection effects.
Patent Information
- Application Number
- CN202411730661.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-29
AI Technical Summary
Existing polyurethane foam materials are flammable, have poor fire resistance, and electromagnetic pollution poses harm to human bodies and electronic equipment. It is difficult for existing materials to solve these problems at the same time.
Using a co-extruded foaming plate, the foam core layer is extruded by blending polyurethane masterbatches, flame retardant crosslinking agents, modified magnetic bamboo charcoal powder and additives, and co-extruding with the modified extruded non-foaming surface layer of polyethylene terephthalate, forming a multi-stage crosslinking network to improve the flame retardant, heat insulation, sound insulation and electromagnetic protection properties of the material.
The flame retardant performance, thermal insulation performance, sound insulation performance and electromagnetic protection performance of the material are significantly improved, reducing the risk of combustion and the harm of electromagnetic pollution to the human body and equipment.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic plates, in particular to a co-extruded foam plate and a preparation method thereof. Background Art
[0002] With the development and progress of industry, the world's demand for energy is constantly increasing. The shortage of energy has now become a common problem that needs to be solved globally, and energy conservation and emission reduction have also become a global research issue. Building energy consumption, industrial energy consumption and transportation energy consumption are listed as the three major sources of greenhouse gas emissions in the energy consumption field. Because the thermal insulation performance of buildings is generally poor, the heating consumption is high, which not only pollutes the environment, but also increases energy consumption. Therefore, it is necessary to vigorously promote building energy conservation, and building exterior wall insulation is a very effective way to save energy.
[0003] At present, polystyrene foam, polyurethane rigid foam and the like are commonly used thermal insulation materials. Polyurethane rigid foam occupies a large market share with its advantages of light weight and low thermal conductivity. While being able to maintain temperature, polyurethane rigid foam also has the function of waterproofing. It is a new type of synthetic material with a thermal conductivity of only 0.018~0.023W / (m·K), which is the lowest among all materials currently used for thermal insulation. At the same time, polyurethane foam has good water absorption, excellent cold and heat resistance, and the longest service life. Therefore, polyurethane foam is well-deserved as a giant in thermal insulation wall materials. However, its fatal disadvantage is that it is extremely easy to burn and has extremely poor fire safety performance. It is reported that many fire accidents in various places were ignited by it, causing huge economic losses and casualties. After the major fires, various enhanced and modified studies on polyurethane foam have received a lot of attention. People hope to improve its fire resistance by modifying it, so that it can be used in building materials more safely.
[0004] With the development of science and technology, various electronic devices and electrical products are becoming more and more popular, bringing great convenience to people's daily life. However, during the operation of electronic devices and electrical products, the interaction of electric fields and magnetic fields will generate electromagnetic waves. Electromagnetic waves are colorless and odorless, ubiquitous, and have strong penetrating power. When the electromagnetic radiation generated by electromagnetic waves in a certain space exceeds a certain intensity, electromagnetic pollution will be formed. The main hazards of electromagnetic wave radiation to the human body are as follows: causing endocrine disorders, inducing cell mutations, causing cataracts, causing vision loss or even complete loss, and causing damage to the cardiovascular system and reproductive system. Electromagnetic pollution will not only directly damage human health, but also affect the normal operation of electronic equipment, and further affect people's normal life. Electromagnetic radiation can cause the normal operation of electronic instruments and precision equipment to malfunction, and will interfere with and damage communication signals. For example, when the received signal of a train is interfered by electromagnetic waves during its operation, it may deviate from the track, endangering people's lives and property. In order to reduce electromagnetic pollution, we must limit the intensity of electromagnetic radiation to a certain space or reduce the intensity of electromagnetic radiation to an acceptable range. In addition, electromagnetic shielding materials are an effective measure to deal with electromagnetic pollution. Summary of the invention
[0005] The object of the present invention is to provide a co-extruded foam board and a preparation method thereof, so as to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A co-extruded foamed board, comprising a foamed core layer obtained by foaming and extruding polyurethane masterbatch, flame retardant cross-linking agent, modified magnetic bamboo charcoal powder and auxiliary agent, and a non-foamed surface layer obtained by extruding modified polyethylene terephthalate;
[0008] The polyurethane masterbatch is prepared by reacting diphenylmethane diisocyanate with polycarbonate diol, terminal hydroxyl hydrogen-containing silicone oil, diethylene glycol and ethanol and then granulating.
[0009] The flame retardant cross-linking agent is prepared by reacting hexachlorocyclotriphosphazene with sodium 2-allylphenolate and sodium phenolate;
[0010] The modified magnetic bamboo charcoal powder is prepared by subjecting bamboo powder to secondary carbonization, loading iron oxide compounds and modification with a silane coupling agent;
[0011] The non-foamed surface layer is prepared by extruding polyethylene terephthalate, polyphenyl polymethylene polyisocyanate and ethylene-sodium methacrylate ionomer by blending.
[0012] As an optimization, the polycarbonate diol model is PCDL-5650E, and the molecular weight is 500.
[0013] As an optimization, the terminal hydroxyl hydrogen-containing silicone oil has a weight average molecular weight of 2500 and a hydrogen content of 0.5%.
[0014] As an optimization, the raw material of the bamboo powder is moso bamboo, and the particle size is 100 mesh.
[0015] As an optimization, the polyethylene terephthalate model is EP150, purchased from Jiangsu Yingjiu New Material Technology Co., Ltd.
[0016] As an optimization, the polyphenyl polymethylene polyisocyanate model is Wanhua PM-200.
[0017] As an optimization, the ethylene-sodium methacrylate ionomer model is Surlyn 8320.
[0018] A method for preparing a co-extruded foamed board comprises the following preparation steps:
[0019] (1) Weigh 10-15 parts of diphenylmethane diisocyanate by mass, heat to 60-70°C in a nitrogen atmosphere until it melts, add 0.5-0.8 parts of dibutyltin dilaurate at a rate of 3-5 drops per second, stir at 300-400 r / min for 20-30 min, add 6.99-10.79 parts of polycarbonate diol and 34.96-53.94 parts of terminal hydroxyl hydrogenated silicone oil, react at 60-70°C and 300-400 r / min for 2.5-3 h, and take After confirming that the reaction is complete, add 1.36-1.91 parts of diethylene glycol at 3-5 drops per second, react at 65-75°C, 300-400r / min for 3-4h, take samples to confirm that the reaction is complete, add 0.09-0.13 parts of anhydrous ethanol, reflux at 65-75°C, 350-450r / min for 2-3h, take samples to confirm that there is no free isocyanate group, heat at 80°C for 1-2h to evaporate excess ethanol, pass into a single-screw extruder, granulate, and obtain polyurethane masterbatch;
[0020] (2) The bamboo powder was cleaned by ultrasonic vibration for 2-3 h, dried at 60-70 °C for 3-4 h, soaked in a mixed solution of ethanol / toluene with a volume ratio of 1:2 at a material-liquid ratio of 1:(3-4) for 10-14 h, centrifuged at 5000-6000 rpm for 10-12 min, and the precipitate was vacuum dried at 60-70 °C for 4-5 h. The precipitate was added to a tube furnace, heated to 1000 °C at a heating rate of 5 °C / min in a nitrogen atmosphere, and calcined for 1 h. The charcoal powder was naturally cooled to 200 °C, the outer cover of the tube furnace was opened, and the charcoal powder was accelerated to room temperature. The charcoal powder was passed through a 40-mesh sieve to obtain bamboo charcoal powder.
[0021] (3) adding bamboo charcoal powder to an iron salt solution at a material-liquid ratio of 1:(4-5) and soaking for 2-3 hours, centrifuging at 5000-6000 rpm for 10-12 minutes, vacuum drying the precipitate at 60-70°C for 4-5 hours, immersing it in a 10 wt% sodium hydroxide solution at a material-liquid ratio of 1:(4-5), soaking for 2-3 hours, filtering, washing with pure water 3-4 times, vacuum drying at 70-80°C for 10-12 hours, adding it to a tubular furnace, heating it to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcining it for 2 hours, naturally cooling it to 200°C, opening the outer cover of the tubular furnace, accelerating cooling it to room temperature, adding it to a high-speed pulverizer for pulverization, and passing it through a 150-200 mesh sieve to obtain secondary carbonized magnetic bamboo charcoal powder;
[0022] (4) Disperse 1 part of secondary carbonized magnetic bamboo charcoal powder in 9-12 parts of toluene by weight, and ultrasonically disperse for 30-40 min at room temperature, add 0.5-0.6 parts of vinyl tri(2-methoxyethoxy)silane, and ultrasonically disperse for 3-5 min. Reflux in a water bath at 70-80°C and 200-300 r / min for 6-8 h, filter, wash alternately with anhydrous ethanol and pure water for 3-5 times, and vacuum dry at 50-60°C for 6-8 h to obtain modified magnetic bamboo charcoal powder.
[0023] (5) In nitrogen atmosphere, 34.8 parts of hexachlorocyclotriphosphazene and 90-100 parts of anhydrous tetrahydrofuran were mixed by weight, stirred at 200-300 r / min until dissolved, 46.85 parts of sodium 2-allylphenolate were added, refluxed at 70-80°C for 6-8h, 40.63 parts of sodium phenolate were added, refluxed for 20-24h, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure to remove tetrahydrofuran, 70-80 parts of dichloromethane were added, stirred at 200-300 r / min at room temperature until dissolved, washed alternately with 5wt% sodium chloride solution and pure water until neutral, 15-20 parts of anhydrous magnesium sulfate were added, dried for 10-12h, filtered, and the filtrate was distilled under reduced pressure to obtain a flame retardant crosslinking agent;
[0024] (6) According to the mass percentage, 70 parts of polyurethane masterbatch, 15 parts of flame retardant crosslinking agent, 15 parts of modified magnetic bamboo charcoal powder, 0.5 parts of chloroplatinic acid, and 2 parts of curing agent were mixed evenly in a high-speed mixer, added into a supercritical microporous foaming two-stage extruder as a foaming core layer, and 8-11 MPa of carbon dioxide was introduced. The temperature of the twin screw was set to 220-240°C and the speed was 50-60 rpm. The temperature of the single screw was set to 190-210°C and the speed was 50-60 rpm. pm, 30-40 parts of polyethylene terephthalate, 0.43-0.57 parts of polyphenyl polymethylene polyisocyanate, and 0.37-0.49 parts of ethylene-sodium methacrylate ionomer are mixed evenly in a high-speed mixer, added into a twin-screw extruder as a non-foamed surface layer for extrusion, the processing temperature is set to 250-280°C, the rotation speed is 50-60rpm, the foamed core layer and the non-foamed surface layer are co-extruded, and after molding, pulling, and cutting, a co-extruded foamed board is obtained.
[0025] As an optimization, the iron salt solution in step (3) is a mixed solution of 0.9 mol / L ferric chloride and 0.45 mol / L ferrous chloride.
[0026] As an optimization, the curing agent in step (6) is methyl ethyl ketone peroxide.
[0027] As an optimization, the co-extrusion of the foamed core layer and the non-foamed surface layer in step (6) can be combined in any number of layers and layer thickness.
[0028] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0029] When preparing the co-extruded foaming board, the present invention firstly reacts diphenylmethane diisocyanate with polycarbonate diol, terminal hydroxyl hydrogen-containing silicone oil, diethylene glycol and ethanol to prepare polyurethane master batch; bamboo powder is subjected to secondary carbonization, loaded with iron oxide compound and modified with silane coupling agent to obtain modified magnetic bamboo charcoal powder; hexachlorocyclotriphosphazene is reacted with sodium 2-allylphenol and sodium phenol to obtain a flame retardant crosslinking agent; the polyurethane master batch is mixed with the modified magnetic bamboo charcoal powder and the flame retardant crosslinking agent, and then extruded and foamed by supercritical carbon dioxide as a foaming core layer, and co-extruded with a non-foaming surface layer of polyethylene terephthalate that is modified and extruded to obtain the co-extruded foaming board.
[0030] Firstly, diphenylmethane diisocyanate reacts with polycarbonate diol, terminal hydroxyl hydrogen-containing silicone oil, diethylene glycol and ethanol under the action of a catalyst dibutyltin dilaurate to obtain polyurethane, wherein the terminal hydroxyl hydrogen-containing silicone oil contains silicon-hydrogen bonds, and undergoes silicon-hydrogen addition reaction with carbon-carbon double bonds of other components under the catalysis of chloroplatinic acid during subsequent foaming and extrusion. At the same time, the excess of hydroxyl groups is controlled in this reaction to obtain a portion of hydroxyl-terminated polyurethane segments.
[0031] Secondly, after the bamboo powder is carbonized once, it is soaked in an iron salt solution and a sodium hydroxide solution in sequence and then carbonized for the second time to obtain a secondary carbonized magnetic bamboo charcoal powder loaded with iron oxide compounds, which is then modified using a vinyl silane coupling agent to obtain a modified magnetic bamboo charcoal powder, which has good electromagnetic absorption function and improves dispersibility and compatibility in organic matter; hexachlorocyclotriphosphazene is reacted with sodium 2-allylphenol and sodium phenol to obtain a flame retardant cross-linking agent, the phosphorus and nitrogen elements contained in it have excellent synergistic flame retardant effects, which can effectively improve the flame retardant properties of the product, and at the same time has three carbon-carbon double bonds, which can form a complex cross-linking network, and the six benzene rings on it have a strong rigid structure, which also improves the mechanical strength of the product.
[0032] Finally, the polyurethane masterbatch, modified magnetic bamboo charcoal powder, flame retardant crosslinking agent, chloroplatinic acid, and methyl ethyl ketone peroxide are blended and foamed and extruded using supercritical carbon dioxide microporous foaming technology as a foaming core layer, wherein under the action of chloroplatinic acid and methyl ethyl ketone peroxide, the silicon-hydrogen bonds in the polyurethane masterbatch, the carbon-carbon double bonds on the modified magnetic bamboo charcoal powder, and the carbon-carbon double bonds on the flame retardant crosslinking agent undergo a complex multi-stage crosslinking reaction to form a multi-stage crosslinking network with the modified magnetic bamboo charcoal powder as the core, the polyurethane as the skeleton, and the flame retardant crosslinking agent as the connection point, and the crosslinking reaction and the foaming reaction are carried out simultaneously. In the foaming process, a large number of bubbles can be formed in the melt in the early stage because the crosslinking reaction is not deep and the melt strength is low. Then, as the crosslinking reaction deepens, the melt strength gradually increases, and the bubbles that have been formed are difficult to break through the bubble wall to form open pores. , and the cell diameter is also limited as the melt strength increases, and finally an excellent foaming material with large cell density and small cell diameter is formed; the non-foaming surface layer has good stability in use, and food-grade polyethylene terephthalate is extruded, and polyphenyl polymethylene polyisocyanate and ethylene-sodium methacrylate ionomer are added for blending, and chain extension is performed while promoting crystallization, thereby improving the bending strength and impact strength of the non-foaming surface layer. At the contact interface between the non-foaming surface layer and the foaming core layer, polyphenyl polymethylene polyisocyanate reacts with polyethylene terephthalate and polyurethane at the same time, and the prepared polyurethane has a partially hydroxyl-terminated chain segment, which can participate in the covalent bond cross-linking reaction, so that in addition to the physical contact and mixing, the non-foaming surface layer and the foaming core layer have increased covalent bond bonding, which has a significant effect on the improvement of bending strength and impact strength. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0034] The co-extruded foamed boards in all the following embodiments and comparative examples are made into a three-layer structure, with two outer layers being non-foamed surface layers and a foamed core layer in the middle. The thickness of the non-foamed surface layer is (3±0.2) mm, and the thickness of the foamed core layer is (10±0.2) mm. Example
[0035] A method for preparing a co-extruded foamed board, the method comprising the following steps:
[0036] (1) Weigh 10 parts of diphenylmethane diisocyanate by mass, heat to 60°C under nitrogen atmosphere until melted, add 0.5 parts of dibutyltin dilaurate at 3 drops per second, stir at 300 r / min for 30 min, add 6.99 parts of polycarbonate diol and 34.96 parts of terminal hydroxyl hydrogenated silicone oil, react at 60°C and 300 r / min for 3 h, take samples to confirm complete reaction, add 1.36 parts of diethylene glycol at 3 drops per second, react at 65°C and 300 r / min for 4 h, take samples to confirm complete reaction, add 0.09 parts of anhydrous ethanol, reflux at 65°C and 350 r / min for 3 h, take samples to confirm no free isocyanate groups, heat at 80°C for 2 h to evaporate excess ethanol, pass into a single screw extruder, granulate, and obtain polyurethane masterbatch;
[0037] (2) The bamboo powder was cleaned by ultrasonic vibration for 2 h, dried at 60 ° C for 4 h, immersed in a mixed solution of ethanol / toluene with a volume ratio of 1:2 and a solid-liquid ratio of 1:3 for 14 h, centrifuged at 5000 rpm for 12 min, and the precipitate was vacuum dried at 60 ° C for 5 h. The precipitate was added to a tube furnace and heated to 1000 ° C at a heating rate of 5 ° C / min in a nitrogen atmosphere and calcined for 1 h. The charcoal powder was naturally cooled to 200 ° C, the outer cover of the tube furnace was opened, and the charcoal powder was accelerated to room temperature. The charcoal powder was sieved through a 40-mesh sieve to obtain bamboo charcoal powder.
[0038] (3) adding bamboo charcoal powder to an iron salt solution at a material-liquid ratio of 1:4 and soaking for 3 hours, centrifuging at 5000 rpm for 12 minutes, vacuum drying the precipitate at 60°C for 5 hours, immersing it in a 10 wt% sodium hydroxide solution at a material-liquid ratio of 1:4, soaking for 3 hours, filtering, washing with pure water for 3 times, vacuum drying at 70°C for 12 hours, adding it to a tubular furnace, heating it to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcining it for 2 hours, naturally cooling it to 200°C, opening the outer cover of the tubular furnace, accelerating cooling it to room temperature, adding it to a high-speed pulverizer for pulverization, and passing it through a 150-mesh sieve to obtain secondary carbonized magnetic bamboo charcoal powder;
[0039] (4) Disperse 1 part of secondary carbonized magnetic bamboo charcoal powder in 9 parts of toluene by weight, perform ultrasonic dispersion at room temperature for 40 min, add 0.5 parts of vinyl tri(2-methoxyethoxy)silane, perform ultrasonic dispersion for 3 min, reflux in a water bath at 70°C and 200 r / min for 8 h, filter, wash alternately with anhydrous ethanol and pure water for 3 times, and dry in a vacuum at 50°C for 8 h to obtain modified magnetic bamboo charcoal powder;
[0040] (5) In nitrogen atmosphere, 34.8 parts of hexachlorocyclotriphosphazene and 90 parts of anhydrous tetrahydrofuran were mixed by weight, stirred at 200 r / min until dissolved, 46.85 parts of sodium 2-allylphenolate were added, refluxed at 70°C for 6 h, 40.63 parts of sodium phenolate were added, refluxed for 20 h, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure to remove tetrahydrofuran, 70 parts of dichloromethane were added, stirred at 200 r / min at room temperature until dissolved, washed alternately with 5wt% sodium chloride solution and pure water until neutral, 15 parts of anhydrous magnesium sulfate were added, dried for 12 h, filtered, and the filtrate was distilled under reduced pressure to obtain a flame retardant crosslinking agent;
[0041] (6) According to the weight percentage, 70 parts of polyurethane masterbatch, 15 parts of flame retardant crosslinking agent, 15 parts of modified magnetic bamboo charcoal powder, 0.5 parts of chloroplatinic acid and 2 parts of methyl ethyl ketone peroxide were mixed evenly in a high-speed mixer, and added to a supercritical microporous foaming two-stage extruder for extrusion as a foaming core layer. 8 MPa of carbon dioxide was introduced, the temperature of the twin screw was set to 220°C and the speed was 50 rpm, and the temperature of the single screw was set to 190°C and the speed was 50 rpm. 30 parts of polyethylene terephthalate, 0.43 parts of polyphenyl polymethylene polyisocyanate and 0.37 parts of ethylene-sodium methacrylate ionomer were mixed evenly in a high-speed mixer, and added to a twin screw extruder for extrusion as a non-foaming surface layer. The processing temperature was set to 250°C and the speed was 50 rpm. The foaming core layer and the non-foaming surface layer were co-extruded, and after molding, pulling and cutting, a co-extruded foamed board was obtained. Example
[0042] A method for preparing a co-extruded foamed board, the method comprising the following steps:
[0043] (1) Weigh 12 parts of diphenylmethane diisocyanate by mass, heat to 65°C under nitrogen atmosphere until melted, add 0.63 parts of dibutyltin dilaurate at 4 drops per second, stir at 350 r / min for 25 min, add 7.19 parts of polycarbonate diol and 41.96 parts of terminal hydroxyl hydrogenated silicone oil, react at 65°C and 350 r / min for 2.5 h, take samples to confirm complete reaction, add 1.88 parts of diethylene glycol at 4 drops per second, react at 70°C and 350 r / min for 3.5 h, take samples to confirm complete reaction, add 0.11 parts of anhydrous ethanol, reflux at 70°C and 400 r / min for 2.5 h, take samples to confirm no free isocyanate groups, heat at 80°C for 1.5 h to evaporate excess ethanol, pass into a single screw extruder, granulate, and obtain polyurethane masterbatch;
[0044] (2) The bamboo powder was cleaned by ultrasonic vibration for 2.5 h, dried at 65 °C for 3.5 h, immersed in a mixed solution of ethanol / toluene with a volume ratio of 1:2 and a solid-liquid ratio of 1:3.5 for 12 h, centrifuged at 5500 rpm for 11 min, and the precipitate was vacuum dried at 65 °C for 4.5 h. The precipitate was added to a tube furnace and heated to 1000 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and calcined for 1 h. The precipitate was naturally cooled to 200 °C, the outer cover of the tube furnace was opened, and the precipitate was accelerated to cool to room temperature. The precipitate was sieved through a 40-mesh sieve to obtain bamboo charcoal powder.
[0045] (3) adding the bamboo charcoal powder to an iron salt solution at a material-liquid ratio of 1:4.5, soaking it for 2.5 hours, centrifuging it at 5500 rpm for 11 minutes, vacuum drying the precipitate at 65°C for 4.5 hours, immersing it in a 10 wt% sodium hydroxide solution at a material-liquid ratio of 1:4.5, soaking it for 2.5 hours, filtering it, washing it with pure water for 3.5 times, vacuum drying it at 75°C for 11 hours, adding it to a tubular furnace, heating it to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcining it for 2 hours, naturally cooling it to 200°C, opening the outer cover of the tubular furnace, accelerating cooling it to room temperature, adding it to a high-speed pulverizer for pulverization, and passing it through a 180-mesh sieve to obtain secondary carbonized magnetic bamboo charcoal powder;
[0046] (4) Disperse 1 part of secondary carbonized magnetic bamboo charcoal powder in 10 parts of toluene by weight, perform ultrasonic dispersion at room temperature for 35 min, add 0.55 parts of vinyl tri(2-methoxyethoxy)silane, perform ultrasonic dispersion for 4 min, reflux in a water bath at 75°C and 250 r / min for 7 h, filter, wash with anhydrous ethanol and pure water alternately for 4 times, and vacuum dry at 55°C for 7 h to obtain modified magnetic bamboo charcoal powder;
[0047] (5) In nitrogen atmosphere, 34.8 parts of hexachlorocyclotriphosphazene and 95 parts of anhydrous tetrahydrofuran were mixed by weight, stirred at 250 r / min until dissolved, 46.85 parts of sodium 2-allylphenolate were added, refluxed at 75°C for 7 h, 40.63 parts of sodium phenolate were added, refluxed for 22 h, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure to remove tetrahydrofuran, 75 parts of dichloromethane were added, stirred at 250 r / min at room temperature until dissolved, washed alternately with 5wt% sodium chloride solution and pure water until neutral, 18 parts of anhydrous magnesium sulfate were added, dried for 11 h, filtered, and the filtrate was distilled under reduced pressure to obtain a flame retardant crosslinking agent;
[0048] (6) According to the weight percentage, 70 parts of polyurethane masterbatch, 15 parts of flame retardant crosslinking agent, 15 parts of modified magnetic bamboo charcoal powder, 0.5 parts of chloroplatinic acid and 2 parts of methyl ethyl ketone peroxide were mixed uniformly in a high-speed mixer, and added to a supercritical microporous foaming two-stage extruder for extrusion as a foaming core layer. 9.5 MPa of carbon dioxide was introduced, the temperature of the twin screw was set to 230°C and the speed was 55 rpm, and the temperature of the single screw was set to 200°C and the speed was 55 rpm. 35 parts of polyethylene terephthalate, 0.50 parts of polyphenyl polymethylene polyisocyanate and 0.43 parts of ethylene-sodium methacrylate ionomer were mixed uniformly in a high-speed mixer, and added to a twin screw extruder for extrusion as a non-foaming surface layer. The processing temperature was set to 270°C and the speed was 55 rpm. The foaming core layer and the non-foaming surface layer were co-extruded, and after molding, pulling and cutting, a co-extruded foamed board was obtained. Example
[0049] A method for preparing a co-extruded foamed board, the method comprising the following steps:
[0050] (1) 15 parts of diphenylmethane diisocyanate were weighed by weight, heated to 70°C under nitrogen atmosphere until melted, 0.8 parts of dibutyltin dilaurate were added dropwise at 5 drops per second, stirred at 400 r / min for 20 min, 10.79 parts of polycarbonate diol and 53.94 parts of terminal hydroxyl hydrogenated silicone oil were added, and the mixture was reacted at 70°C and 400 r / min for 2.5 h. After sampling to confirm complete reaction, 1.91 parts of diethylene glycol were added dropwise at 5 drops per second, and the mixture was reacted at 75°C and 400 r / min for 3 h. After sampling to confirm complete reaction, 0.13 parts of anhydrous ethanol were added, and the mixture was refluxed at 75°C and 450 r / min for 2 h. After sampling to confirm no free isocyanate group, the mixture was heated at 80°C for 1 h to evaporate excess ethanol, and the mixture was passed into a single screw extruder for granulation to obtain a polyurethane masterbatch;
[0051] (2) The bamboo powder was cleaned by ultrasonic vibration for 3 h, dried at 70 °C for 3 h, immersed in a mixed solution of ethanol / toluene with a volume ratio of 1:2 and a material-liquid ratio of 1:4 for 14 h, centrifuged at 6000 rpm for 10 min, and the precipitate was vacuum dried at 70 °C for 5 h. The precipitate was added to a tube furnace and heated to 1000 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and calcined for 1 h. The precipitate was naturally cooled to 200 °C, the outer cover of the tube furnace was opened, and the precipitate was accelerated to cool to room temperature. The precipitate was sieved through a 40-mesh sieve to obtain bamboo charcoal powder.
[0052] (3) adding the bamboo charcoal powder to an iron salt solution at a material-liquid ratio of 1:5 and soaking for 2 hours, centrifuging at 6000 rpm for 10 minutes, vacuum drying the precipitate at 70°C for 4 hours, immersing it in a 10 wt% sodium hydroxide solution at a material-liquid ratio of 1:5, soaking for 2 hours, filtering, washing with pure water for 4 times, vacuum drying at 80°C for 10 hours, adding it to a tubular furnace, heating it to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcining it for 2 hours, naturally cooling it to 200°C, opening the outer cover of the tubular furnace, accelerating cooling it to room temperature, adding it to a high-speed pulverizer for pulverization, and passing it through a 200-mesh sieve to obtain secondary carbonized magnetic bamboo charcoal powder;
[0053] (4) Disperse 1 part of secondary carbonized magnetic bamboo charcoal powder in 12 parts of toluene by weight, perform ultrasonic dispersion at room temperature for 30 min, add 0.6 parts of vinyl tri(2-methoxyethoxy)silane, perform ultrasonic dispersion for 5 min, reflux in a water bath at 80°C and 300 r / min for 6 h, filter, wash alternately with anhydrous ethanol and pure water for 5 times, and vacuum dry at 60°C for 6 h to obtain modified magnetic bamboo charcoal powder;
[0054] (5) In nitrogen atmosphere, 34.8 parts of hexachlorocyclotriphosphazene and 100 parts of anhydrous tetrahydrofuran were mixed by weight, stirred at 300 r / min until dissolved, 46.85 parts of sodium 2-allylphenolate were added, refluxed at 80°C for 6 h, 40.63 parts of sodium phenolate were added, refluxed for 24 h, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure to remove tetrahydrofuran, 80 parts of dichloromethane were added, stirred at 300 r / min at room temperature until dissolved, washed alternately with 5wt% sodium chloride solution and pure water until neutral, 20 parts of anhydrous magnesium sulfate were added, dried for 10 h, filtered, and the filtrate was distilled under reduced pressure to obtain a flame retardant crosslinking agent;
[0055] (6) According to the weight percentage, 70 parts of polyurethane masterbatch, 15 parts of flame retardant crosslinking agent, 15 parts of modified magnetic bamboo charcoal powder, 0.5 parts of chloroplatinic acid and 2 parts of methyl ethyl ketone peroxide were mixed uniformly in a high-speed mixer, and added to a supercritical microporous foaming two-stage extruder for extrusion as a foaming core layer. 11MPa of carbon dioxide was introduced, the temperature of the twin screw was set to 240°C and the speed was 60rpm, and the temperature of the single screw was set to 210°C and the speed was 60rpm. 40 parts of polyethylene terephthalate, 0.57 parts of polyphenyl polymethylene polyisocyanate and 0.49 parts of ethylene-sodium methacrylate ionomer were mixed uniformly in a high-speed mixer, and added to a twin screw extruder for extrusion as a non-foaming surface layer. The processing temperature was set to 280°C and the speed was 60rpm. The foaming core layer and the non-foaming surface layer were co-extruded, and after molding, pulling and cutting, a co-extruded foamed board was obtained.
[0056] Comparative Example 1
[0057] A method for preparing a co-extruded foamed board, the method comprising the following steps:
[0058] (1) Weigh 10 parts of diphenylmethane diisocyanate by mass, heat to 60°C under nitrogen atmosphere until melted, add 0.5 parts of dibutyltin dilaurate at 3 drops per second, stir at 300 r / min for 30 min, add 6.99 parts of polycarbonate diol and 34.96 parts of terminal hydroxyl hydrogenated silicone oil, react at 60°C and 300 r / min for 3 h, take samples to confirm complete reaction, add 1.36 parts of diethylene glycol at 3 drops per second, react at 65°C and 300 r / min for 4 h, take samples to confirm complete reaction, add 0.09 parts of anhydrous ethanol, reflux at 65°C and 350 r / min for 3 h, take samples to confirm no free isocyanate groups, heat at 80°C for 2 h to evaporate excess ethanol, pass into a single screw extruder, granulate, and obtain polyurethane masterbatch;
[0059] (2) The bamboo powder was cleaned by ultrasonic vibration for 2 h, dried at 60 ° C for 4 h, immersed in a mixed solution of ethanol / toluene with a volume ratio of 1:2 and a solid-liquid ratio of 1:3 for 14 h, centrifuged at 5000 rpm for 12 min, and the precipitate was vacuum dried at 60 ° C for 5 h. The precipitate was added to a tube furnace and heated to 1000 ° C at a heating rate of 5 ° C / min in a nitrogen atmosphere and calcined for 1 h. The charcoal powder was naturally cooled to 200 ° C, the outer cover of the tube furnace was opened, and the charcoal powder was accelerated to room temperature. The charcoal powder was sieved through a 40-mesh sieve to obtain bamboo charcoal powder.
[0060] (3) adding bamboo charcoal powder to an iron salt solution at a material-liquid ratio of 1:4 and soaking for 3 hours, centrifuging at 5000 rpm for 12 minutes, vacuum drying the precipitate at 60°C for 5 hours, immersing it in a 10 wt% sodium hydroxide solution at a material-liquid ratio of 1:4, soaking for 3 hours, filtering, washing with pure water for 3 times, vacuum drying at 70°C for 12 hours, adding it to a tubular furnace, heating it to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcining it for 2 hours, naturally cooling it to 200°C, opening the outer cover of the tubular furnace, accelerating cooling it to room temperature, adding it to a high-speed pulverizer for pulverization, and passing it through a 150-mesh sieve to obtain secondary carbonized magnetic bamboo charcoal powder;
[0061] (4) Disperse 1 part of secondary carbonized magnetic bamboo charcoal powder in 9 parts of toluene by weight, perform ultrasonic dispersion at room temperature for 40 min, add 0.5 parts of vinyl tri(2-methoxyethoxy)silane, perform ultrasonic dispersion for 3 min, reflux in a water bath at 70°C and 200 r / min for 8 h, filter, wash alternately with anhydrous ethanol and pure water for 3 times, and dry in a vacuum at 50°C for 8 h to obtain modified magnetic bamboo charcoal powder;
[0062] (5) According to the weight percentage, 75 parts of polyurethane masterbatch, 10 parts of 1,5-hexadiene, 15 parts of modified magnetic bamboo charcoal powder, 0.5 parts of chloroplatinic acid and 2 parts of methyl ethyl ketone peroxide were mixed uniformly in a high-speed mixer, and added to a supercritical microporous foaming two-stage extruder for extrusion as a foaming core layer. 8 MPa of carbon dioxide was introduced, and the temperature of the twin screw was set to 220°C and the speed was 50 rpm. The temperature of the single screw was set to 190°C and the speed was 50 rpm. 30 parts of polyethylene terephthalate, 0.43 parts of polyphenyl polymethylene polyisocyanate and 0.37 parts of ethylene-sodium methacrylate ionomer were mixed uniformly in a high-speed mixer, and added to a twin screw extruder for extrusion as a non-foaming surface layer. The processing temperature was set to 250°C and the speed was 50 rpm. The foaming core layer and the non-foaming surface layer were co-extruded. After molding, pulling and cutting, a co-extruded foamed board was obtained.
[0063] Comparative Example 2
[0064] A method for preparing a co-extruded foamed board, the method comprising the following steps:
[0065] (1) Weigh 10 parts of diphenylmethane diisocyanate by mass, heat to 60°C under nitrogen atmosphere until melted, add 0.5 parts of dibutyltin dilaurate at 3 drops per second, stir at 300 r / min for 30 min, add 6.99 parts of polycarbonate diol and 34.96 parts of terminal hydroxyl hydrogenated silicone oil, react at 60°C and 300 r / min for 3 h, take samples to confirm complete reaction, add 1.36 parts of diethylene glycol at 3 drops per second, react at 65°C and 300 r / min for 4 h, take samples to confirm complete reaction, add 0.09 parts of anhydrous ethanol, reflux at 65°C and 350 r / min for 3 h, take samples to confirm no free isocyanate groups, heat at 80°C for 2 h to evaporate excess ethanol, pass into a single screw extruder, granulate, and obtain polyurethane masterbatch;
[0066] (2) In nitrogen atmosphere, 34.8 parts of hexachlorocyclotriphosphazene and 90 parts of anhydrous tetrahydrofuran were mixed by weight, stirred at 200 r / min until dissolved, 46.85 parts of sodium 2-allylphenolate were added, refluxed at 70°C for 6 h, 40.63 parts of sodium phenolate were added, refluxed for 20 h, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure to remove tetrahydrofuran, 70 parts of dichloromethane were added, stirred at 200 r / min at room temperature until dissolved, washed alternately with 5wt% sodium chloride solution and pure water until neutral, 15 parts of anhydrous magnesium sulfate were added, dried for 12 h, filtered, and the filtrate was distilled under reduced pressure to obtain a flame retardant crosslinking agent;
[0067] (3) 85 parts of polyurethane masterbatch, 15 parts of flame retardant crosslinking agent, 0.5 parts of chloroplatinic acid and 2 parts of methyl ethyl ketone peroxide were mixed uniformly in a high-speed mixer, and added to a supercritical microporous foaming two-stage extruder for extrusion as a foaming core layer. 8 MPa of carbon dioxide was introduced, and the temperature of the twin screw was set to 220°C and the speed was 50 rpm. The temperature of the single screw was set to 190°C and the speed was 50 rpm. 30 parts of polyethylene terephthalate, 0.43 parts of polyphenyl polymethylene polyisocyanate and 0.37 parts of ethylene-sodium methacrylate ionomer were mixed uniformly in a high-speed mixer, and added to a twin screw extruder for extrusion as a non-foaming surface layer. The processing temperature was set to 250°C and the speed was 50 rpm. The foaming core layer and the non-foaming surface layer were co-extruded, and after molding, pulling and cutting, a co-extruded foamed board was obtained.
[0068] Comparative Example 3
[0069] A method for preparing a co-extruded foamed board, the method comprising the following steps:
[0070] (1) 10 parts of diphenylmethane diisocyanate were weighed by weight, heated to 60°C under nitrogen atmosphere until melted, 0.5 parts of dibutyltin dilaurate were added dropwise at 3 drops per second, stirred at 300 r / min for 30 min, 6.39 parts of polycarbonate diol and 31.97 parts of terminal hydroxyl hydrogenated silicone oil were added, and the mixture was reacted at 60°C and 300 r / min for 3 h. After sampling to confirm complete reaction, 1.27 parts of diethylene glycol were added dropwise at 3 drops per second, and the mixture was reacted at 65°C and 300 r / min for 4 h. After sampling to confirm complete reaction, 0.15 parts of anhydrous ethanol were added, and the mixture was refluxed at 65°C and 350 r / min for 3 h. After sampling to confirm no free isocyanate group, the mixture was heated at 80°C for 2 h to evaporate excess ethanol, and the mixture was passed into a single screw extruder for granulation to obtain a polyurethane masterbatch;
[0071] (2) The bamboo powder was cleaned by ultrasonic vibration for 2 h, dried at 60 ° C for 4 h, immersed in a mixed solution of ethanol / toluene with a volume ratio of 1:2 and a solid-liquid ratio of 1:3 for 14 h, centrifuged at 5000 rpm for 12 min, and the precipitate was vacuum dried at 60 ° C for 5 h. The precipitate was added to a tube furnace and heated to 1000 ° C at a heating rate of 5 ° C / min in a nitrogen atmosphere and calcined for 1 h. The charcoal powder was naturally cooled to 200 ° C, the outer cover of the tube furnace was opened, and the charcoal powder was accelerated to room temperature. The charcoal powder was sieved through a 40-mesh sieve to obtain bamboo charcoal powder.
[0072] (3) adding bamboo charcoal powder to an iron salt solution at a material-liquid ratio of 1:4 and soaking for 3 hours, centrifuging at 5000 rpm for 12 minutes, vacuum drying the precipitate at 60°C for 5 hours, immersing it in a 10 wt% sodium hydroxide solution at a material-liquid ratio of 1:4, soaking for 3 hours, filtering, washing with pure water for 3 times, vacuum drying at 70°C for 12 hours, adding it to a tubular furnace, heating it to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcining it for 2 hours, naturally cooling it to 200°C, opening the outer cover of the tubular furnace, accelerating cooling it to room temperature, adding it to a high-speed pulverizer for pulverization, and passing it through a 150-mesh sieve to obtain secondary carbonized magnetic bamboo charcoal powder;
[0073] (4) Disperse 1 part of secondary carbonized magnetic bamboo charcoal powder in 9 parts of toluene by weight, perform ultrasonic dispersion at room temperature for 40 min, add 0.5 parts of vinyl tri(2-methoxyethoxy)silane, perform ultrasonic dispersion for 3 min, reflux in a water bath at 70°C and 200 r / min for 8 h, filter, wash alternately with anhydrous ethanol and pure water for 3 times, and dry in a vacuum at 50°C for 8 h to obtain modified magnetic bamboo charcoal powder;
[0074] (5) In nitrogen atmosphere, 34.8 parts of hexachlorocyclotriphosphazene and 90 parts of anhydrous tetrahydrofuran were mixed by weight, stirred at 200 r / min until dissolved, 46.85 parts of sodium 2-allylphenolate were added, refluxed at 70°C for 6 h, 40.63 parts of sodium phenolate were added, refluxed for 20 h, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure to remove tetrahydrofuran, 70 parts of dichloromethane were added, stirred at 200 r / min at room temperature until dissolved, washed alternately with 5wt% sodium chloride solution and pure water until neutral, 15 parts of anhydrous magnesium sulfate were added, dried for 12 h, filtered, and the filtrate was distilled under reduced pressure to obtain a flame retardant crosslinking agent;
[0075] (6) According to the weight percentage, 70 parts of polyurethane masterbatch, 15 parts of flame retardant crosslinking agent, 15 parts of modified magnetic bamboo charcoal powder, 0.5 parts of chloroplatinic acid and 2 parts of methyl ethyl ketone peroxide were mixed evenly in a high-speed mixer, and added to a supercritical microporous foaming two-stage extruder for extrusion as a foaming core layer. 8 MPa of carbon dioxide was introduced, the temperature of the twin screw was set to 220°C and the speed was 50 rpm, and the temperature of the single screw was set to 190°C and the speed was 50 rpm. 30 parts of polyethylene terephthalate, 0.43 parts of polyphenyl polymethylene polyisocyanate and 0.37 parts of ethylene-sodium methacrylate ionomer were mixed evenly in a high-speed mixer, and added to a twin screw extruder for extrusion as a non-foaming surface layer. The processing temperature was set to 250°C and the speed was 50 rpm. The foaming core layer and the non-foaming surface layer were co-extruded, and after molding, pulling and cutting, a co-extruded foamed board was obtained.
[0076] Comparative Example 4
[0077] A method for preparing a co-extruded foamed board, the method comprising the following steps:
[0078] (1) Weigh 10 parts of diphenylmethane diisocyanate by mass, heat to 60°C under nitrogen atmosphere until melted, add 0.5 parts of dibutyltin dilaurate at 3 drops per second, stir at 300 r / min for 30 min, add 6.99 parts of polycarbonate diol and 34.96 parts of terminal hydroxyl hydrogenated silicone oil, react at 60°C and 300 r / min for 3 h, take samples to confirm complete reaction, add 1.36 parts of diethylene glycol at 3 drops per second, react at 65°C and 300 r / min for 4 h, take samples to confirm complete reaction, add 0.09 parts of anhydrous ethanol, reflux at 65°C and 350 r / min for 3 h, take samples to confirm no free isocyanate groups, heat at 80°C for 2 h to evaporate excess ethanol, pass into a single screw extruder, granulate, and obtain polyurethane masterbatch;
[0079] (2) The bamboo powder was cleaned by ultrasonic vibration for 2 h, dried at 60 ° C for 4 h, immersed in a mixed solution of ethanol / toluene with a volume ratio of 1:2 and a solid-liquid ratio of 1:3 for 14 h, centrifuged at 5000 rpm for 12 min, and the precipitate was vacuum dried at 60 ° C for 5 h. The precipitate was added to a tube furnace and heated to 1000 ° C at a heating rate of 5 ° C / min in a nitrogen atmosphere and calcined for 1 h. The charcoal powder was naturally cooled to 200 ° C, the outer cover of the tube furnace was opened, and the charcoal powder was accelerated to room temperature. The charcoal powder was sieved through a 40-mesh sieve to obtain bamboo charcoal powder.
[0080] (3) adding bamboo charcoal powder to an iron salt solution at a material-liquid ratio of 1:4 and soaking for 3 hours, centrifuging at 5000 rpm for 12 minutes, vacuum drying the precipitate at 60°C for 5 hours, immersing it in a 10 wt% sodium hydroxide solution at a material-liquid ratio of 1:4, soaking for 3 hours, filtering, washing with pure water for 3 times, vacuum drying at 70°C for 12 hours, adding it to a tubular furnace, heating it to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcining it for 2 hours, naturally cooling it to 200°C, opening the outer cover of the tubular furnace, accelerating cooling it to room temperature, adding it to a high-speed pulverizer for pulverization, and passing it through a 150-mesh sieve to obtain secondary carbonized magnetic bamboo charcoal powder;
[0081] (4) Disperse 1 part of secondary carbonized magnetic bamboo charcoal powder in 9 parts of toluene by weight, perform ultrasonic dispersion at room temperature for 40 min, add 0.5 parts of vinyl tri(2-methoxyethoxy)silane, perform ultrasonic dispersion for 3 min, reflux in a water bath at 70°C and 200 r / min for 8 h, filter, wash alternately with anhydrous ethanol and pure water for 3 times, and dry in a vacuum at 50°C for 8 h to obtain modified magnetic bamboo charcoal powder;
[0082] (5) In nitrogen atmosphere, 34.8 parts of hexachlorocyclotriphosphazene and 90 parts of anhydrous tetrahydrofuran were mixed by weight, stirred at 200 r / min until dissolved, 46.85 parts of sodium 2-allylphenolate were added, refluxed at 70°C for 6 h, 40.63 parts of sodium phenolate were added, refluxed for 20 h, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure to remove tetrahydrofuran, 70 parts of dichloromethane were added, stirred at 200 r / min at room temperature until dissolved, washed alternately with 5wt% sodium chloride solution and pure water until neutral, 15 parts of anhydrous magnesium sulfate were added, dried for 12 h, filtered, and the filtrate was distilled under reduced pressure to obtain a flame retardant crosslinking agent;
[0083] (6) According to the parts by mass, 70 parts of polyurethane masterbatch, 15 parts of flame retardant crosslinking agent, 15 parts of modified magnetic bamboo charcoal powder, 0.5 parts of chloroplatinic acid and 2 parts of methyl ethyl ketone peroxide were mixed uniformly in a high-speed mixer, and added to a supercritical microporous foaming two-stage extruder for extrusion as a foaming core layer. 8 MPa of carbon dioxide was introduced, and the temperature of the twin screw was set to 220°C and the speed was 50 rpm. The temperature of the single screw was set to 190°C and the speed was 50 rpm. 30 parts of polyethylene terephthalate were added to the twin screw extruder for extrusion as a non-foaming surface layer. The processing temperature was set to 250°C and the speed was 50 rpm. The foaming core layer and the non-foaming surface layer were co-extruded. After molding, pulling and cutting, a co-extruded foamed board was obtained.
[0084] Test Example 1
[0085] Mechanical properties test: The bending strength and impact strength of the prepared co-extruded foam board are tested to evaluate its mechanical properties. The specific test methods are as follows:
[0086] Bending strength test: refer to GB / T 9341-2008 for testing, measure in the vertical direction of the non-foamed surface, the test speed is (20±2) mm / min, record the bending strength data, and take the average value of 5 samples in each test.
[0087] Impact strength test: refer to GB / T 1043.1-2008 for testing. The specimen is a non-notched type I specimen. Take the original thickness of the board and impact the non-foamed surface. Record the impact strength data. Test 5 specimens in each group and take the average value.
[0088] The results are shown in Table 1.
[0089] Table 1
[0090] Bending strength / MPa <![CDATA[Impact strength / kJ·m -2 > Example 1 82.34 23.4 Example 2 80.49 21.6 Example 3 83.61 22.3 Comparative Example 1 76.42 20.3 Comparative Example 2 72.45 19.5 Comparative Example 3 66.28 16.2 Comparative Example 4 63.15 11.7
[0091] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the co-extruded foamed board prepared by the present invention has good bending strength and impact strength.
[0092] By comparing the data in the table, the use of the prepared flame retardant cross-linking agent and modified magnetic bamboo charcoal powder can effectively improve the flexural strength and impact strength. When the diol in the foaming core layer is excessive, it can be covalently bonded with the non-foaming surface layer to improve the mechanical properties. The modification of the non-foaming surface layer also effectively improves the flexural strength and impact strength.
[0093] Test Example 2
[0094] Functional performance test: Test the combustion performance level, thermal conductivity, sound insulation coefficient, and electromagnetic absorption coefficient of the co-extruded foam board to evaluate its flame retardancy, heat insulation, sound insulation, and electromagnetic protection performance. The specific test methods are as follows:
[0095] Flame retardant test: Test according to GB8624-2012, determine the combustion performance level of the co-extruded foam board according to the method described therein, and record the data.
[0096] Thermal insulation test: Cut the samples into a size of 300mm×300mm, use the original thickness, and use a DRP-6W thermal conductivity tester for testing. Record the measured thermal conductivity and take the average value of 5 samples in each test.
[0097] Sound insulation test: The sound insulation performance test was carried out in accordance with GB / Z 27764-2011. The samples were tested in a large-diameter impedance tube with a diameter of 100mm and a test frequency of 100-1600Hz and a small-diameter impedance tube with a diameter of 30mm and a test frequency of 1600-6300Hz. The test data were analyzed and fitted using VA-Lab4 software, and the average sound insulation was recorded in dB. The average value was taken for each group of 5 samples tested.
[0098] Electromagnetic protection test: refer to the shielding room method in GB / T 30142-2013 to test the electromagnetic shielding effectiveness of the material, record the data, and take the average value of 5 samples in each test.
[0099] The results are shown in Table 2.
[0100] Table 2
[0101] Combustion performance level <![CDATA[Thermal conductivity / W·m -1 ·K -1 > Average sound insulation / dB Electromagnetic shielding effectiveness / dB Example 1 B1 0.0194 46.2 51.4 Example 2 B1 0.0187 45.4 52.3 Example 3 B1 0.0196 46.8 51.8 Comparative Example 1 B3 0.0244 37.5 50.6 Comparative Example 2 B1 0.0263 28.4 3.4 Comparative Example 3 B1 0.0191 44.7 51.2 Comparative Example 4 B1 0.0202 45.6 53.4
[0102] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the co-extruded foam board prepared by the present invention has good flame retardancy, heat insulation, sound insulation and electromagnetic shielding properties.
[0103] By comparing the data in the table, the addition of flame retardant cross-linking agent effectively improves the flame retardant properties of the co-extruded foamed board, and at the same time synergizes with the modified magnetic bamboo charcoal powder to enhance the foaming effect and improve the heat insulation and sound insulation effects. The addition of modified magnetic bamboo charcoal powder also brings excellent electromagnetic shielding properties, which can effectively protect the human body from electromagnetic radiation damage.
[0104] Test Example 3
[0105] Foaming performance test: Test the cell density and cell diameter to evaluate the foaming condition and basic performance of the co-extruded foam board. The specific test method is as follows:
[0106] Cell micro-morphology test: Use an ultra-thin blade to cut the foam core layer sample, then perform gold spraying, use a scanning electron microscope to take photos, use image processing software to analyze the photos, and statistically analyze the cell diameter and cell density of the foam core layer. The cell diameter statistics should be no less than 100 holes, and record the average cell diameter and cell density data.
[0107] The results are shown in Table 3.
[0108] Table 3
[0109] Average cell diameter / μm <![CDATA[Cell density / cells·cm -3 > Example 1 70.27 <![CDATA[3.8×10 6 ]]> Example 2 78.35 <![CDATA[2.4×10 6 ]]> Example 3 84.18 <![CDATA[1.7×10 6 ]]> Comparative Example 1 183.49 <![CDATA[8.4×10 5 ]]> Comparative Example 2 296.83 <![CDATA[4.9×10 4 ]]> Comparative Example 3 76.48 <![CDATA[3.4×10 6 ]]> Comparative Example 4 75.61 <![CDATA[4.2×10 6 ]]>
[0110] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the co-extruded foamed board prepared by the present invention has good foaming performance.
[0111] By comparing the data in the table, the flame retardant cross-linking agent and the modified magnetic bamboo charcoal powder work synergistically to form a cross-linking network, and the foaming condition is controlled by the degree of cross-linking to improve the foaming effect of the foaming core layer.
[0112] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A co-extruded foam board, characterized in that: The co-extruded foaming board comprises a foaming core layer formed by foaming and extruding polyurethane masterbatch, flame retardant cross-linking agent, modified magnetic bamboo charcoal powder and additives, and a non-foaming surface layer formed by extruding modified polyethylene terephthalate; The polyurethane masterbatch is prepared by reacting diphenylmethane diisocyanate with polycarbonate diol, terminal hydroxyl hydrogen-containing silicone oil, diethylene glycol and ethanol and then granulating. The flame retardant cross-linking agent is prepared by reacting hexachlorocyclotriphosphazene with sodium 2-allylphenolate and sodium phenolate; The modified magnetic bamboo charcoal powder is prepared by subjecting bamboo powder to secondary carbonization, loading iron oxide compounds and modification with a silane coupling agent; The non-foamed surface layer is prepared by extruding polyethylene terephthalate, polyphenyl polymethylene polyisocyanate and ethylene-sodium methacrylate ionomer by blending.
2. A co-extruded foamed board according to claim 1, characterized in that: The polycarbonate diol model is PCDL-5650E.
3. The co-extruded foamed board according to claim 1, characterized in that: The terminal hydroxyl hydrogen-containing silicone oil has a weight average molecular weight of 2500 and a hydrogen content of 0.5%.
4. The co-extruded foamed board according to claim 1, characterized in that: The polyethylene terephthalate model is EP150.
5. The co-extruded foamed board according to claim 1, characterized in that: The polyphenyl polymethylene polyisocyanate model is Wanhua PM-200.
6. The co-extruded foamed board according to claim 1, characterized in that: The model of the ethylene-sodium methacrylate ionomer is Surlyn 8320.
7. A method for preparing a co-extruded foamed board, characterized in that: The method comprises the following preparation steps: (1) Weigh 10-15 parts of diphenylmethane diisocyanate by mass, heat to 60-70°C in a nitrogen atmosphere until it melts, add 0.5-0.8 parts of dibutyltin dilaurate at a rate of 3-5 drops per second, stir at 300-400 r / min for 20-30 min, add 6.99-10.79 parts of polycarbonate diol and 34.96-53.94 parts of terminal hydroxyl hydrogenated silicone oil, react at 60-70°C and 300-400 r / min for 2.5-3 h, and take After confirming that the reaction is complete, add 1.36-1.91 parts of diethylene glycol at 3-5 drops per second, react at 65-75°C, 300-400r / min for 3-4h, take samples to confirm that the reaction is complete, add 0.09-0.13 parts of anhydrous ethanol, reflux at 65-75°C, 350-450r / min for 2-3h, take samples to confirm that there is no free isocyanate group, heat at 80°C for 1-2h to evaporate excess ethanol, pass into a single-screw extruder, granulate, and obtain polyurethane masterbatch; (2) The bamboo powder was cleaned by ultrasonic vibration for 2-3 h, dried at 60-70 °C for 3-4 h, soaked in a mixed solution of ethanol / toluene with a volume ratio of 1:2 at a material-liquid ratio of 1:(3-4) for 10-14 h, centrifuged at 5000-6000 rpm for 10-12 min, and the precipitate was vacuum dried at 60-70 °C for 4-5 h. The precipitate was added to a tube furnace, heated to 1000 °C at a heating rate of 5 °C / min in a nitrogen atmosphere, and calcined for 1 h. The charcoal powder was naturally cooled to 200 °C, the outer cover of the tube furnace was opened, and the charcoal powder was accelerated to room temperature. The charcoal powder was passed through a 40-mesh sieve to obtain bamboo charcoal powder. (3) adding bamboo charcoal powder to an iron salt solution at a material-liquid ratio of 1:(4-5) and soaking for 2-3 hours, centrifuging at 5000-6000 rpm for 10-12 minutes, vacuum drying the precipitate at 60-70°C for 4-5 hours, immersing it in a 10 wt% sodium hydroxide solution at a material-liquid ratio of 1:(4-5), soaking for 2-3 hours, filtering, washing with pure water 3-4 times, vacuum drying at 70-80°C for 10-12 hours, adding it to a tubular furnace, heating it to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcining it for 2 hours, naturally cooling it to 200°C, opening the outer cover of the tubular furnace, accelerating cooling it to room temperature, adding it to a high-speed pulverizer for pulverization, and passing it through a 150-200 mesh sieve to obtain secondary carbonized magnetic bamboo charcoal powder; (4) Disperse 1 part of secondary carbonized magnetic bamboo charcoal powder in 9-12 parts of toluene by weight, and ultrasonically disperse for 30-40 min at room temperature, add 0.5-0.6 parts of vinyl tri(2-methoxyethoxy)silane, and ultrasonically disperse for 3-5 min. Reflux in a water bath at 70-80°C and 200-300 r / min for 6-8 h, filter, wash alternately with anhydrous ethanol and pure water for 3-5 times, and vacuum dry at 50-60°C for 6-8 h to obtain modified magnetic bamboo charcoal powder. (5) In nitrogen atmosphere, 34.8 parts of hexachlorocyclotriphosphazene and 90-100 parts of anhydrous tetrahydrofuran were mixed by weight, stirred at 200-300 r / min until dissolved, 46.85 parts of sodium 2-allylphenolate were added, refluxed at 70-80°C for 6-8h, 40.63 parts of sodium phenolate were added, refluxed for 20-24h, cooled naturally to room temperature, filtered, and the filtrate was distilled under reduced pressure to remove tetrahydrofuran, 70-80 parts of dichloromethane were added, stirred at 200-300 r / min at room temperature until dissolved, washed alternately with 5wt% sodium chloride solution and pure water until neutral, 15-20 parts of anhydrous magnesium sulfate were added, dried for 10-12h, filtered, and the filtrate was distilled under reduced pressure to obtain a flame retardant crosslinking agent; (6) According to the mass percentage, 70 parts of polyurethane masterbatch, 15 parts of flame retardant crosslinking agent, 15 parts of modified magnetic bamboo charcoal powder, 0.5 parts of chloroplatinic acid, and 2 parts of curing agent were mixed evenly in a high-speed mixer, added into a supercritical microporous foaming two-stage extruder as a foaming core layer, and 8-11 MPa of carbon dioxide was introduced. The temperature of the twin screw was set to 220-240°C and the speed was 50-60 rpm. The temperature of the single screw was set to 190-210°C and the speed was 50-60 rpm. pm, 30-40 parts of polyethylene terephthalate, 0.43-0.57 parts of polyphenyl polymethylene polyisocyanate, and 0.37-0.49 parts of ethylene-sodium methacrylate ionomer are mixed evenly in a high-speed mixer, added into a twin-screw extruder as a non-foamed surface layer for extrusion, the processing temperature is set to 250-280°C, the rotation speed is 50-60rpm, the foamed core layer and the non-foamed surface layer are co-extruded, and after molding, pulling, and cutting, a co-extruded foamed board is obtained.
8. The method for preparing a co-extruded foamed board according to claim 7, characterized in that: The iron salt solution in step (3) is a mixed solution of 0.9 mol / L ferric chloride and 0.45 mol / L ferrous chloride.
9. The method for preparing a co-extruded foamed board according to claim 7, characterized in that: The curing agent in step (6) is methyl ethyl ketone peroxide.
10. The method for preparing a co-extruded foamed board according to claim 7, characterized in that: In step (6), the foamed core layer and the non-foamed surface layer are co-extruded in any number of layers and thickness.
Citation Information
Patent Citations
Production method of polyurethane foam molded article
CN101080444A
Synthesis method of tris (2-allylphenoxy)-triphenoxy cyclotriphosphazene
CN117430637A